Infection of the Laboratory Mouse with the Intracellular Pathogen Ehrlichia chaffeensis - Winslow, Gary M. (American Society for Microbiology, 1998)
To determine the basis of susceptibility and resistance to human monocytic ehrlichiosis (HME), immunocompetent and immunocompromised mice were infected with Ehrlichia chaffeensis and bacterial loads were measured by PCR and by immunohistochemistry. Immunocompetent (C.B-17 and C57BL/6) mice cleared the bacteria within 10 days, but immunocompromised SCID and SCID/BEIGE mice developed persistent infection in the spleen, liver, peritoneal cavity, brain, lung, and bone marrow and became moribund within 24 days. Both immunocompromised strains lack T and B lymphocytes, but the SCID/BEIGE strain is also deficient in natural killer (NK) cell function. During advanced stages of disease, the infections were associated with wasting, splenomegaly, lymphadenopathy, liver granulomas and necroses, intravascular coagulation, and granulomatous inflammation. Histochemical and immunohistochemical localization studies confirmed the presence of bacteria in tissues, and viable bacteria were cultured from infected animals. The data reveal that T and/or B cells play an essential role during resistance of immunocompetent mice to infection with E. chaffeensis and demonstrate the utility of immunocompromised mice as an experimental model for the study of HME.